Recoverable low fluorine content palladium complex-catalyzed Suzuki-Miyaura and Sonogashira coupling reactions under thermomorphic mode. (10th September 2022) - Tessema, Eskedar; Fan, Yao-Wen; Chiu, Chiao-Fan; Elakkat, Vijayanath; Rahayu, Hening Asti; Shen, Chia-Rui; Shanthakumar, Karthik Chimatahalli; Zhang, Peng; Lu, Norman
Abstract: The reaction of [PdCl2 (CH3 CN)2 ] and bis-5, 5'-(Rf CH2 OCH2 )-2, 2′-bpy (1 ), where Rf = n -C4 F8 H, in the presence of dichloromethane (CH2 Cl2 ) resulted in the synthesis of low fluorine content Pd complex, [PdCl2 [5, 5′-bis-(Rf CH2 OCH2 )-2, 2′-bpy] (2 ). The Pd-catalyzed Suzuki-Miyaura and Sonogashira coupling reactions of several aryl halides with their respective reagents were selected to demonstrate the feasibility of catalytic activity and recycling usage with 2 as the catalyst by using dibutyl ether (DBE) as the solvent at 140–145 °C under the thermomorphic mode. The Pd complex 2 -catalyzed Suzuki-Miyaura reactions of different aryl iodides with phenylboronic acid derivatives have showed good recycling results though its activity was observed to decrease after the fifth cycle. Similarly, 2 -catalyzed Sonogashira reactions of several aryl iodides with phenyl acetylene have also displayed good recycling results for a total of up to 8 cycles, with a high yield and TON. The electronic effect studies from substituents in both Suzuki-Miyaura and Sonogashira coupling reactions showed that electron withdrawing groups on the aryl iodide speed up the reaction rate. Furthermore, the catalytic activity of the Pd complex (2 ) showed a better result with the more reactive aryl iodide compared to the less reactive aryl bromide and chloride. To our knowledge, this is the first example of recoverable low fluorine content Pd-catalyzed Suzuki-Miyaura and Sonogashira reactions under the thermomorphic mode. Graphical abstract: Image 1